Evaluation of Operational Waste Management System at Belawan Ocean Fishing Port - Sitompul, Nabila Khairiyah; Siregar, Amos Hamonangan; Hamka , Moh Saiful Rahman; Fitri, Amraini (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2026)
Belawan Ocean Fishing Port plays a strategic role in the capture fisheries management system in western Indonesia. The high intensity of port operational activities contributes to increasing waste generation, which may adversely affect environmental quality and fisheries sustainability. This study aimed to evaluate the operational waste management system at Belawan Ocean Fishing Port and to examine its implications for fisheries management. An exploratory descriptive approach supported by quantitative estimation was applied. Data were collected through field observations, semi structured interviews with ten key informants, and document analysis of relevant regulations and official reports. Waste generation was estimated based on the number of vessels landing daily and the average waste generated per vessel. The results indicate that operational waste at Belawan Ocean Fishing Port consists of solid waste, liquid waste, and hazardous waste. The estimated daily waste generation reached approximately ±800 kg of solid waste, ±2.5 m³ of liquid waste, and ±10 liters of hazardous waste. The existing waste management system has not been standardized, as reflected by the absence of waste segregation at the source, non-operational wastewater treatment facilities, and the lack of dedicated facilities for hazardous waste handling. In addition, stakeholder awareness and community participation in waste management remain limited. This study concludes that operational waste management at Belawan Ocean Fishing Port has not been fully integrated into fishing port governance. Strengthening infrastructure, institutional capacity, and participatory approaches is therefore essential to support sustainable fisheries management in the port area.